Gangguan Memori pada Pasien Meningioma - Wisnu R Danu N, Lalu; Pangestika, Anindhita (CV RIFAINSTITUT, 2021)
Brain tumor patients often experience cognitive impairment. In the case of meningiomas, this disorder can affect areas of executive function and memory. Cognitive impairment in meningioma patients is influenced by the location and volume of the tumor. In a study of 38 patients with WHO grade I meningiomas, working memory capacity was lower in patients with tumor resection without adjuvant treatment compared with healthy controls. The writing of this article includes various sources originating from scientific journals and government guidelines and related agencies. Source searches were carried out on online portals for journal publications such as MedScape, Google Scholar (scholar.google.com) and the National Center for Biotechnology Information (ncbi.nlm.nih.gov), with the keyword “Meningioma”. Another study of 293 patients (220 women and 73 men) with multiple meningiomas showed that 23% of patients after surgery had neurological deficits and 12% had new permanent neurological deficits. Regarding risk factors, one study showed that the frequency of women is higher than that of men. In addition, age is also considered to have an effect on patients with meningiomas. Meningiomas are intracranial brain tumors that are often found in adults. Cognitive deficits are common in brain tumor patients. At least one area of ​​cognition is impaired in brain tumor patients.